Manufacturing Review and Flight-Test Evaluation of the AQUILA Fixed-Wing Remotely Piloted Vehicle - Thato Elijah; Rui Vasconcellos (Tinta Emas Publisher, 2026)
Aircraft are now not only used as a means of transportation and military, but also used as recreational and research tools. One of them is the Unmanned Aerial Vehicle or Remote-Controlled Vehicle, which is a flying vehicle that is controlled remotely by the pilot and can fly manually or autonomously. In this study, modifications were made to the fixed wing RPV structure to previous research. These modifications focused on redesigning the RPV design, RPV manufacturing processes, and flight tests. The results of design modifications made include changing the fuselage design to twin tail boom and adding holes covered with clear acrylic on the floor fuselage to accommodate camera placement and changes in size on the wing chord and wingspan. During the second flight test, the aircraft suffered damage to the nose, stabilizer, and entire wing so that improvements and reinforcement were added to the structure of the nose fuselage, spar, leading edge wing, vertical stabilizer, and horizontal stabilizer. In addition, aluminum tube reinforcement was also added to both tail booms. In the last flight test after the repair, the aircraft was able to fly high but due to the lack of input from the less powerful servo ailerons the aircraft to be difficult to control and eventually crashed.